Associations of self-reported hearing problems with long-term trajectories of mental and functional health in middle-aged and older adults: The role of self-perceptions of aging - Markus Wettstein; Ann-Kristin Reinhard; Bettina Williger; Susanne Wurm (PLoS ONE, 2025)
Impaired hearing is a frequent stressful experience in later life. However, not all individuals affected by hearing problems exhibit restrictions in mental or functional health; there may be psychosocial resources that buffer the detrimental impact of impaired hearing to some extent. We investigate whether positive self-perceptions of aging (SPA, i. e. perceptions of more ongoing development and perceptions of less physical and social losses) do in fact constitute a compensatory resource and moderate between-person and within-person associations of self-reported hearing problems with trajectories of mental and functional health. Our sample comprised n = 9,705 participants in the German Ageing Survey (mean age = 62.41 years, SD = 11.58, range 40-93 years) who were assessed up to five times between 2008 and 2021. Based on longitudinal multilevel regression models, controlling for socio-demographic variables, hearing aid use, and chronic diseases, we found that individuals with overall more hearing problems reported poorer mental health. Moreover, with regard to the within-person associations, on measurement occasions when individuals reported more hearing problems, their mental and functional health was poorer. The association of more hearing problems with poorer functional health was weaker among individuals with lower perceptions of physical loss at baseline (i.e., year 2008). Among chronologically older adults, the association of more hearing problems with poorer functional health was weaker for those with higher perceptions of ongoing development at baseline. Our findings suggest that SPA related to fewer physical losses and to more ongoing development may buffer the negative impact of hearing problems on functional health.